Criminal Law Dilemmas in Withholding and Withdrawal of Intensive Care - Korošec, Damjan (Medicine, Law & Society, 2016)
Regarding the question under which conditions a physician in Slovenia is allowed to omit life-prolonging medical treatment of dying patients, the main legal source is the Patient Rights Act, adopted in Slovenia in 2008 (parallel to Criminal Code of Slovenia). Under this law, there are two possible circumstances in deciding about life-prolonging medical treatment regarding dying patients: a) on the basis of the so-called patient’s testament in the sense of Art. 34 of the Patient Rights Act; and b) without any known patient's testament in the sense of Art. 34 of the Patient Rights Act. Such decisions can also be contrary to a decisive wish of relatives of the dying patient to prolong the patient’s life under all circumstances. If this decision is reached with full respect of the Patient Rights Act as well as the rules of medical science, omitting life prolonging medical treatment cannot be unlawful in the sense of medical criminal law.
Keywords: cubstantive criminal law; omission; life prolonging medical treatment; Slovenia